Políticas de educação infantil e escola em tempo integral : entre a formulação legal e a prática cotidiana - Maffi, Marla Maria Debastiani (2009)
The text points resulted of a research that objectified to verify the relevancy of the politics of integral time for schools of infantile education, raising potential and limits of such politics, walking between the practical legal formularization and daily in the reality of a city located in the north the Rio Grande do Sul State. The adopted methodology can be considered qualitative and happened on the procedure of the participant comment, carried through in the context of a municipal school of Infantile Education that received the fictitious name from 'Yellow' , in view of that in the method of the participant comment the searching collection given and to information through the interaction and comment of the situations of the daily life of a group. The instruments of the research had been the memories and notebook of field produced by the researcher in process of the daily and systematic interaction with the research citizens: the pertaining to school community affects to this school, throughout the year of 2008. Initially categories of analysis had been detached, between which the routine was characterized as base of quarrels. As conclusion, the research report points that is not enough to extend the time of learning permanence in the school, if this time if not to make to follow for a consistent educative project, that allows to place the axle of the pertaining to school organization in the pedagogical sector, that is, in the interests and necessities of the child, overlapping them it the interests of financial rationalization of the administrations and the character 'small day-care center' historically marked for the assistencial character.